Applying international guidelines for calcium supplementation to prevent pre-eclampsia: simulation of recommended dosages suggests risk of excess intake in Ethiopia. Issue 3 (15th October 2018) - Tesfaye, Biniyam; Sinclair, Kate; Wuehler, Sara E; Moges, Tibebu; De-Regil, Luz Maria; Dickin, Katherine L
Abstract: Objective: To simulate impact of Ca supplementation on estimated total Ca intakes among women in a population with low dietary Ca intakes, using WHO recommendations: 1·5–2·0 g elemental Ca/d during pregnancy to prevent pre-eclampsia. Design: Single cross-sectional 24 h dietary recall data were adjusted using IMAPP software to simulate proportions of women who would meet or exceed the Estimated Average Requirement (EAR) and Tolerable Upper Intake Level (UL) assuming full or partial adherence to WHO guidelines. Setting: Nationally and regionally representative data, Ethiopia's 'lean' season 2011. Subjects: Women 15–45 years ( n 7908, of whom 492 pregnant). Results: National mean usual Ca intake was 501 (sd 244) mg/d. Approximately 89, 91 and 96 % of all women, pregnant women and 15–18 years, respectively, had dietary Ca intakes below the EAR. Simulating 100 % adherence to 1·0, 1·5 and 2·0 g/d estimated nearly all women (>99 %) would meet the EAR, regardless of dosage. Nationally, supplementation with 1·5 and 2·0 g/d would result in intake exceeding the UL in 3·7 and 43·2 % of women, respectively, while at 1·0 g/d those exceeding the UL would be <1 % (0·74 %) except in one region (4·95 %). Conclusions: Most Ethiopian women consume insufficient Ca, increasing risk of pre-eclampsia. Providing Ca supplements of 1·5–2·0 g/d could result in high proportions of women exceeding the UL, while universal consumption of 1·0 g/d would meet requirements with minimal risk of excess. Appropriately tested screening tools could identify and reduce risk to high Ca consumers. Research on minimum effective Ca supplementation to prevent pre-eclampsia is also needed to determine whether lower doses could be recommended.